SEHAT BERSAMA TOGA DI ERA PANDEMI COVID-19 - Risdiana Chandra Dhewy; Dewi Sukriyah (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2021)
Most people want their yard to be planted with plants so that the atmosphere becomes beautiful and natural. However, filling the yard with nutritious plants is sometimes still rarely done. On the other hand, medicinal plants are very useful and easy to plant in the yard. Therefore, lecturers and students of STKIP PGRI SIDOARJO held TOGA Cultivation as an effort towards healthy families in Jiken Village, Tulangan. By holding this activity, villagers participated and were very enthusiastic considering the many benefits of TOGA, especially during a pandemic like now. At least the benefits of TOGA can increase the body's immunity. Not only as a medicine, TOGA can also be used to complement dishes.